Hubungan antara Kepemimpinan Transformasional dan Iklim Komunikasi Organisasi di SMK Kehutanan dan Seni St. Fransiskus Xaverius Maumere - Maria Viviana Nurak Lewar; Sahrul Hidayat; Tibertha Archangela Ghiriani; Helena Aprilia Andini; Agustinus Irfanto; Agnes Monika Anyela (Jurnal Ilmiah Ekonomi, Akuntansi, dan Pajak, 2025)
This report aims to describe the application of transformational leadership and its influence on the organizational communication climate at the St. Francis Xaverius Maumere Forestry and Arts Vocational School. Using a descriptive narrative method through interviews and observations, this report illustrates how principals are implementing transformational leadership in school management. The results of the study show that school principals are able to provide inspiration through example, motivation, and continuous support to teachers and education staff. This leadership practice is reflected in the giving of trust, the involvement of teachers in decision-making, and the encouragement to innovate in the learning process. The organizational communication climate in schools is considered open, transparent, and supportive, so that teachers and staff feel comfortable conveying ideas, criticisms, and suggestions without fear. Effective communication between leaders, teachers, and staff helps strengthen teamwork and increase a sense of ownership of the school's vision and mission. Thus, transformational leadership plays an important role in creating a positive organizational communication climate and supporting the improvement of performance and quality of education in schools.